Trend of Population Change in Nepal and its Adverse Effect on Diverse Aspects - Singh, Laxman (Journal of Educational Research and Innovation, 2024)
This research paper aims to describe the trend of population change and its adverse effects on diverse aspects of individual, family, community and the nation. Secondary data have been used from the statistical reports of various census conducted in Nepal in this study. This study has focused on the trend of population change from the initial census 1911 to the last census year 2021 with its adverse effects on human being. Nepal’s population was under the 6 million in initial census year 1911. After during the 110-years period later, as per a latest statistical report 2021, the current population has crossed 29 million due to high birth and low death rate, poor use of contraceptives, illiteracy, unemployment, poverty, low status of women, traditional system of marriage, cultural and religious beliefs, increasing trend of immigration and regional or provincial difference which contributes to create environmental degradation, possibility of extinction, rise in unemployment, lack of education, high cost of living, conflict and wars, deterioration of culture, lower life expectancy and quality of life. The feeling of risk resulting from the large population size in Nepal is same as other developing countries. Looking at the current demographic situation as compared with limited resources in Nepal, it is suggested that the exceptional population influencing policies and programs should be formulated and implemented in every regions or residences to combat against adverse effect of overpopulation.